2014
DOI: 10.1016/j.micpath.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Candida albicans hyphal wall protein 1 (HWP1) genotype on biofilm production and fungal susceptibility to microglial cells

Abstract: The hyphal wall protein 1 (HWP1) gene of Candida albicans encodes for a fungal cell wall protein, required for hyphal development and yeast adhesion to epithelial cells; yet, its role in pathogenesis remains largely unknown. In the present study, we analyzed two C. albicans laboratory strains, the DAY286 (HWP1/HWP1) and the null mutant FJS24 (hwp1/hwp1) and six clinical isolates [3 harbouring the homozygous HWP1 gene (HWP1/HWP1) and 3 the heterologous gene (HWP1/hwp1)]. Biofilm production, fungal HWP1 mRNA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 43 publications
(56 reference statements)
2
41
0
1
Order By: Relevance
“…The down-regulations of HWP1 and ECE1 by 6-gingerol or 6-shogaol are consistent with their observed effects on biofilm formation and hyphal development. HWP1 encodes a hyphal wall protein that is essential for hyphal development (Nobile et al, 2006b) and intercellular adherence (Orsi et al, 2014). Previously, we reported that camphor and fenchyl alcohol from cedar leaf oil (Manoharan et al, 2017b) and alizarin from the roots of the madder genus (Manoharan et al, 2017a) inhibit C. albicans biofilm formation by reducing hyphal formation by suppressing the gene expressions of HWP1 and ECE1 .…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulations of HWP1 and ECE1 by 6-gingerol or 6-shogaol are consistent with their observed effects on biofilm formation and hyphal development. HWP1 encodes a hyphal wall protein that is essential for hyphal development (Nobile et al, 2006b) and intercellular adherence (Orsi et al, 2014). Previously, we reported that camphor and fenchyl alcohol from cedar leaf oil (Manoharan et al, 2017b) and alizarin from the roots of the madder genus (Manoharan et al, 2017a) inhibit C. albicans biofilm formation by reducing hyphal formation by suppressing the gene expressions of HWP1 and ECE1 .…”
Section: Discussionmentioning
confidence: 99%
“…108 Biofilm formation seems to protect C. albicans from microglial damage impairing fungal cell phagocytosis, cytokine release, and NO production. 109 The b-glucans on the surface of C. albicans are detected by TLR-2 and 4, as well as Dectin-1 expressed on the surface of retinal and intraparenchymal microglia. [110][111][112] However, these carbohydrates may attenuate TLRmediated NF-kB activation, decreasing the capacity of microglia to release inflammatory cytokines in response to the pathogen.…”
Section: Candidiasismentioning
confidence: 99%
“…Proteomics analysis of biofilm matrix isolated using this optimized method revealed the presence of specific proteins (including glyceraldehyde 3-phosphate dehydrogenase and pyruvate kinase) in the biofilm matrix. Additional Candida genes implicated in biofilm formation include ACE2 ( 93 ), YWP1 ( 94 ), HWP1 ( 95 ), LL34 ( RIX7 ) ( 96 ), ALS3 ( 97 , 98 ), GAL10 ( 99 ), VPS1 ( 100 ), SUR7 ( 101 ), GUP1 ( 102 ), PEP12 ( 103 ), TPK1/2 ( 104 ), NRG1 (transcriptional repressor) and its target BRG1 (GATA family transcription factor) ( 105 ), UME6 (transcriptional regulator), HGC1 (a cyclin-related protein), SUN41 (a putative cell wall glycosidase), EFG1 ( 106 , 107 ), STV1 and VPH1 (Golgi/vacuolar subunits of vacuolar proton-translocating ATPase isoforms) ( 108 ), CEK1 (map kinase) ( 109 ), CDK8 ( 88 ), BCR1 ( 110 ), SPT20 ( 111 ), and SAC1 (PIP phosphatase) ( 112 ). In addition, quorum sensing molecules (such as 3R-hydroxy-tetradecaenoic acid [3R-HTDE, a beta-oxidation metabolite of endogenously present linoleic acid] [ 113 ]), farnesol ( 114117 ), and cis -2-dodecenoic acid (BDSF) ( 118 ) and metabolic processes (e.g., carbohydrate assimilation, amino acid metabolism, and intracellular transport) ( 119 ) and glycolytic flux and hypoxia adaptation ( 120 ) have been suggested to play critical roles in Candida biofilm formation.…”
Section: Factors Influencing Biofilm Formation and Architecturementioning
confidence: 99%